Cognitive impairment among cancer patients experiencing chemotherapy - Bin Alam, Mohammad Zayeed; Hossain, Md Shahanur (Dhaka University Journal of Biological Sciences, 2022)
The aim of the present study was to investigate whether chemotherapy had any particular role on cognitive impairment i.e. difficulties in executive functioning, working memory, naming ability, attention, language, abstraction, orientation, and visuo-spatial constructional and recall ability, among cancer patients in Bangladesh. Sixty cancer patients and thirty healthy individuals were recruited for this study by purposive sampling. Among these cancer patients 30 had experienced chemotherapy and remain 30 had experienced radiotherapy/ surgery/no treatment at all. We used Rey-Osterrieth Complex Figure test and Montreal Cognitive Assessment to investigate cognitive impairment and Bangla version of Depression, Anxiety and Stress Scale to assess emotional distress. Findings revealed that cancer patients in general experience significantly more cognitive difficulties than healthy individuals. Regarding the attention, visual and auditory memory and executive ability the problems are more dominant. Chemotherapy group performed in all aspects of cognitive testing significantly lower than other treatment group. Statistical tests indicated no role of emotional distress on neuropsychological performance. Males with cancer are more vulnerable to cognitive impairment. In a nutshell, this study indicates that cancer patients in Bangladesh experience cognitive impairment and especially patients treated with chemotherapy are more likely to experience cognitive impairment. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 453-464, 2022 (June)